The impact of Environmental History on current Spanish Historiography (2010-2019) - Martín Torres, Alberto (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
The global changes of late twentieth century led to a questioning of the hegemonic paradigms of the major historiographic schools. Along with the crisis of the modernisation paradigm, climate change became an issue and a new historiographic paradigm emerged to face the environmental crisis: Environmental History. Starting with a reflection about the origins and international development, this paper seeks to describe the main foundations of Environmental History and how this new form of studying history has made his way into the Spanish historiography. It includes a brief review of the impact of this new historical current in Spanish historical studies, its evolution and some of the authors working on this field.